FOMO SEBAGAI REFLEKSI KRISIS HARGA DIRI: TINJAUAN INTEGRATIF PSIKOLOGI MODERN DAN NILAI ISLAM - Wantomo Diar Gumelar; Khoirul Mubin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The phenomenon of Fear of Missing Out (FoMO) has emerged as a significant psychosocial impact experienced by generation Z in the digital era, primarily due to their high dependence on social validation through social media. FoMO is closely related to low self-esteem, where individuals tend to experience social anxiety and psychological pressure from feeling left out of others’ social experiences. This study aims to examine FoMO as a manifestation of a self-esteem crisis and to offer an integration between modern psychological approaches and Islamic spiritual values as an alternative solution. The method used is qualitative research with a library research approach, analyzing contemporary psychological theories and the Islamic concept of self-worth. The findings show that FoMO is a response to unstable self-esteem that relies heavily on social approval. Individuals with low self-esteem are more vulnerable to digital pressure and social comparison. Islamic values such as izzah (dignity), muru’ah (moral integrity), and iḥsān (spiritual awareness) offer a more stable and transcendental paradigm of self-worth. This integration provides a holistic approach to strengthening the psychological resilience of generation Z amid the growing FoMO phenomenon.